Institutional Inertia - Valderrama, Laura (IMF Working Papers; Working Paper ;, 2009)
We study the relative efficiency of outside-owned versus employee-owned firms and analyze implications for institutional change in a context of technological innovation. When decisions are made through majority voting, the vote on technology choice is used to influence the later vote on the sharing rule. We show how this dynamic voting generates a systematic technological bias that is contingent on firm ownership. We provide conditions under which the pivotal voter's political leverage leads the firm to an institutional trap whereby majority voting and inefficient technology choice reinforce each other, leading to institutional inertia.